PREDIKSI KEBANKRUTAN PADA PERUSAHAAN AUTOMOTIVE AND ALLIANCES YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN MENGGUNAKAN ANALISA DISKRIMINAN (Z-SCORE) - Putri, Farida Eka; Champaca, Mychelia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the level of corporate bankruptcy using discriminant analysis in automotive companies listed on the Indonesia Stock Exchange. Because automotive companies have a considerable role in the Indonesian economy. This study uses discriminant analysis (Z-score) to see how the predictions of bankruptcy period 2008-2010 in automotive companies. Calculating each bankruptcy prediction on each company totaling 17 companies. The data used in this study were obtained annual financial statements in the book Indonesian Capital Market Directory. The analysis technique used is discriminant analysis using the variables of the Altman Z-score of five is X1 = Net Working Capital to Total Assets, X2 = Retained Earnings to Total Assets, X3 = EBIT to Total Assets, X4 = Market Value of Equity to Book Value of Liabilities and X5 = Sales to Total Assets. It has the formula Z-Score = - 4.267. X_1 x_2 1.26 1.78 1.663 0.842 X_3 X_4 X_5 1.049. With Z-Score criteria> 0.857 categorized as healthy companies <.857 financial distress category. The results of this study indicate that the Altman Z-Score models can be implemented in detecting the possibility of bankruptcy in automotive companies listed on the Indonesia Stock Exchange. Altman Z-Score model and discriminant analysis have similar results in predicting bankruptcy on 17 automotive companies. The results of Z-Score of discriminant analysis on the automotive companies were able to group two categories, namely health and financial distress. During the period of observation shows there are 7 companies included in a healthy condition and as many as 10 companies included in the category of financial distress. Keywords: Financial Distress, Z-Score, Bankruptcy Prediction, Discriminant Analysis